Extraction Algorithm of HOM–LIE Algebras Based on Solvable and Nilpotent Groups - Shadi Shaqaqha; Nadeen Kdaisat (International Journal of Mathematics and Mathematical Sciences)
Dedicated to Al Farouk School & Kinder garten-Irbid-Jordan